PENGARUH ORGANIZATIONAL LEARNIG DAN TIM KERJA TERHADAP KINERJA PEGAWAI DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KOTA PAREPARE - Muh. Ikhsan; Yusuf, Syarifuddin; Syah, Firman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of organizational learning and work teams on the employees performance of the Fire and Rescue Service in Parepare City. The data collection techniques in this study are observation and questionnaires. The research method used is descriptive quantitative method, while the number of samples used in this sample is 118 employees at the Fire and Rescue Service in Parepare City. The results of this study indicate that there is a positive and significant influence between Organizational Learning on the employees performance of the Fire and Rescue Service in Parepare City, there is a positive and significant influence between the Work Team on the employees performance of the Fire and Rescue Service in Parepare City. Thus the hypothesis is proven, as for the effect of the two organizational learning and work team variables are 65%, while the rest is in other variables that are not used in this study.